2020
DOI: 10.1093/gerona/glaa158
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combined Antigravity Treadmill and Conventional Rehabilitation After Hip Fracture in Patients With Sarcopenia

Abstract: Background To compare long-term effects of antigravity treadmill (AGT) combined with conventional rehabilitation (CR) and CR after hip fracture in patients with sarcopenia. Methods Forty-five patients were randomly allocated to AGT combined with CR (experimental group) or CR (control group) for 10 consecutive working days. Participants were evaluated prior to treatment, 3 weeks, 3 months, and 6 months after treatment. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Various definitions of sarcopenia have been developed by different international consensus panels, (the Asian Working Group on Sarcopenia (AWGS), the European Working Group on Sarcopenia in Older People (EWGSOP) and the Foundation of the National Institute of Health, International Working Group on Sarcopenia) each defining cut-off values from mobility limitation measures (appendicular skeletal mass index, grip strength and physical performance). In our review, the authors specifically used the diagnostic criteria included in the AWGS [ 21 , 22 , 23 , 24 , 25 ] and EWGSOP [ 1 , 16 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various definitions of sarcopenia have been developed by different international consensus panels, (the Asian Working Group on Sarcopenia (AWGS), the European Working Group on Sarcopenia in Older People (EWGSOP) and the Foundation of the National Institute of Health, International Working Group on Sarcopenia) each defining cut-off values from mobility limitation measures (appendicular skeletal mass index, grip strength and physical performance). In our review, the authors specifically used the diagnostic criteria included in the AWGS [ 21 , 22 , 23 , 24 , 25 ] and EWGSOP [ 1 , 16 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Study 3 [ 23 ] compared the efficacy of an antigravity treadmill (AGT) combined with conventional physical therapy, and physical therapy alone, in a double-blinded (to outcome) study. Selected patients were 65–90 years old, who had undergone surgery for FNF associated with sarcopenia, according to the AWGS recommendation [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, previous studies have reported that muscle strength exercise and aerobic exercise using an anti-gravity treadmill resulted in improved walking and dynamic balance, while maintaining the same kinetic movement as normal walking and reducing the amount of pressure on the musculoskeletal system [13,15,16]. Thus, anti-gravity treadmill training is an intervention for preventing quadriceps muscle atrophy and for muscle strengthening in patients with femoral fractures [17,18]. Further, it enables partial weight bearing at the initial stage, which may help provide stability for normal gait in the future.…”
Section: Introductionmentioning
confidence: 99%